2021
DOI: 10.1097/md.0000000000024678
|View full text |Cite
|
Sign up to set email alerts
|

Role of tranexamic acid in blood loss control and blood transfusion management of patients undergoing multilevel spine surgery

Abstract: Background: This study aimed to explore the role of tranexamic acid (TXA) in blood loss control and blood transfusion management of patients undergoing multilevel spine surgery. Methods: In this meta-analysis, a comprehensive search of literatures was performed from PubMed, Embase, Cochrane Library, and Web of Science from inception to June 23rd, 2020. Weighed mean difference (WMD) was used as the effect size for measurement data, and risk ratio for enu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
(12 reference statements)
0
19
0
2
Order By: Relevance
“…neurosurgery, though it is a safe and effective means to reduce operative blood loss and blood transfusion rates in cardiac, pulmonary, trauma, obstetric, spinal and orthopaedic surgery. [11][12][13][14] As a synthetic lysine analogue, TXA can modify brain network excitability by activating excitatory ionotropic glutamate receptors. 15 16 On the other hand, TXA may induce hyperexcitability by blocking gamma-aminobutyric acid-driven inhibition of the central nervous system.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…neurosurgery, though it is a safe and effective means to reduce operative blood loss and blood transfusion rates in cardiac, pulmonary, trauma, obstetric, spinal and orthopaedic surgery. [11][12][13][14] As a synthetic lysine analogue, TXA can modify brain network excitability by activating excitatory ionotropic glutamate receptors. 15 16 On the other hand, TXA may induce hyperexcitability by blocking gamma-aminobutyric acid-driven inhibition of the central nervous system.…”
Section: Open Accessmentioning
confidence: 99%
“…TXA is used as a bolus ranging from 10 to 50 mg/kg, followed by a continuous infusion ranging from 1 to 5 mg/kg/hour until the end of the procedures in a variety of neurosurgical procedures 3 8–10. Unfortunately, the risk of postoperative seizures remains uncertain, and restricts the routine use of TXA in neurosurgery, though it is a safe and effective means to reduce operative blood loss and blood transfusion rates in cardiac, pulmonary, trauma, obstetric, spinal and orthopaedic surgery 11–14…”
Section: Introductionmentioning
confidence: 99%
“…Even in more complex, multi-level spine procedures that are especially associated with significant blood loss and can often require blood transfusions, TXA can significantly reduce blood loss and the risk of transfusions in patients undergoing these procedures. 52 , 53 More recent meta-analyses have aggregated RCTs, most prominently those giving IV TXA, in patients undergoing some form of spine surgery, and have further demonstrated that TXA can reduce the risk of blood transfusions in a dose-dependent manner without significantly increasing thrombosis in any circumstance. 48 , 51 However, these results were not observed in a similar meta-analysis including only studies where TXA was given topically, potentially indicating that the route of TXA administration can play a role in the drug’s effectiveness in reducing the risk of transfusions, which contrasts with similar studies in joint surgery.…”
Section: Spine Surgerymentioning
confidence: 99%
“…[3][4][5] This medication has been extensively used in cardiac surgery [6][7][8] and other types of orthopedic surgery, [9][10][11][12][13] including spine surgery. 14,15 Two studies, with large sample sizes of 1,769 and 4,269 pediatric patients undergoing spinal surgery assessed TXA use, but their ndings were limited to TXA e ciency in decreasing blood loss without an analysis of adverse events associated with the drug. 16,17 A few smaller studies, with sample sizes ranging from 44 to 166 patients, reported on the safety of TXA use in this population and did not nd any associated adverse events.…”
Section: Introductionmentioning
confidence: 99%